Coating material and preparation method and application thereof, lithium battery separator
By using functionalized inorganic particles on the lithium-ion battery separator to react with polyamines and acid chlorides, the problems of poor binding performance of inorganic particles and substrates and high cost of aramid materials in the prior art are solved, and high compatibility, uniform coating and low cost effects are achieved.
Patent Information
- Application Number
- CN202311853866.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-29
- Filing Date
- 2023-12-29
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-12-29
AI Technical Summary
The existing lithium-ion battery separator coating materials have problems such as poor bonding performance between inorganic particles and substrates, powder loss and uneven coating. The cost of coating the separator of aramid material is high and has poor compatibility with the separator.
By reacting the functionalized inorganic particles, polyamines and acid chloride in a solvent in the presence of a protective gas, and adding a catalyst, a polymerization promoter and a third monomer, a coating material with high compatibility, uniform coating and low cost is prepared.
Good compatibility between the coating material and the diaphragm is achieved, a continuous and uniform coating is formed, the mechanical strength, puncture strength and thermal stability of the diaphragm are improved, and the cost is reduced, which solves the problem of easy falling off of the inorganic particle-coated diaphragm and high cost of aramid material coated diaphragm.
Smart Images

Figure CN118027395B_ABST
Abstract
Description
Technical field:
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a coating material, a preparation method and application thereof, and a lithium battery separator. Background technology:
[0002] In recent years, in order to achieve sustainable development and protect the ecological environment, lithium-ion battery technology has been widely used. Electric vehicles equipped with lithium-ion power batteries are becoming increasingly popular. In 2021, the sales of new energy vehicles in the Chinese market alone have reached 3.3 million units, and they are still growing rapidly. In 2022, the EU reached an agreement on the plan of "zero carbon dioxide emissions for all passenger cars and light commercial vehicles sold in the EU market from 2035", which is equivalent to banning the sale of gasoline and diesel vehicles from 2035. At the same time, lithium-ion batteries are also widely used in 3C, energy storage and other fields. These data show that lithium-ion batteries will play an increasingly important role in the next decade or even longer.
[0003] The diaphragm is the core component of lithium-ion batteries, which ensures battery safety and is related to electrochemical performance. The mainstream products on the market today are diaphragms made of polyethylene (PE) or polypropylene (PP) as raw materials, and then a heat-resistant inorganic coating is coated on the polyolefin diaphragm. The inorganic particles used for coating include alumina, boehmite, etc. This method has poor bonding performance between the inorganic particles and the substrate, and there are problems such as powder loss and uneven coating. Another method is to coat the polyolefin diaphragm with a heat-resistant polymer coating such as aramid, but the cost is relatively high. Aramid has a large number of benzene rings and hydrogen bond donors and acceptors in the molecular chain, which makes it difficult to construct during the coating process of non-polar polyolefin diaphragms and has poor uniformity.
[0004] Therefore, developing a diaphragm coating material with good compatibility, high coating uniformity and low cost is of great significance to the development of lithium-ion batteries. Summary of the invention:
[0005] In order to solve the problems of poor uniformity and shedding of inorganic particles in the prior art, as well as high cost and poor compatibility of aramid material coating on diaphragms, the present invention provides a coating material, a preparation method and application thereof, and a lithium battery diaphragm.
[0006] In order to achieve the above object, one of the objects of the present invention is to provide a method for preparing a coating material, the preparation method comprising:
[0007] In the presence of a protective gas, the functionalized inorganic particles, the first monomer and the second monomer are subjected to a first reaction in a solvent, and then a catalyst, a polymerization accelerator and a third monomer are added to conduct a second reaction to obtain the coating material;
[0008] The functionalized inorganic particles are inorganic particles with functional groups grafted onto their surfaces, and the functional groups are amino groups and / or carboxyl groups;
[0009] The first monomer is selected from at least one of diamine, triamine and tetraamine;
[0010] The second monomer is selected from at least one of dibasic acid chloride, tribasic acid chloride and tetrabasic acid chloride;
[0011] The structural formula of the third monomer is as follows:
[0012]
[0013] Among them, R 1 , R 2 and R 3 Each independently selected from at least one of a hydrocarbon group, an ether group and an aromatic group; R 4 is selected from an amino group or an acyl chloride group; m≤10, n≤10, p≤10, and m, n and p are not zero at the same time.
[0014] The functionalized inorganic particles are inorganic particles with functional groups grafted onto the surface, and the functional groups are amino groups and / or carboxyl groups.
[0015] A second object of the present invention is to provide a coating material obtained by the aforementioned preparation method.
[0016] The third object of the present invention is to provide the application of the aforementioned coating material in the preparation of lithium battery separators and electrode edge coatings.
[0017] A fourth object of the present invention is to provide a lithium battery separator, comprising a base film and a coating covering one side or both sides of the base film, wherein the base film is a polyolefin separator, and the coating is prepared from the aforementioned coating material.
[0018] The beneficial effects of the present invention are:
[0019] 1. The coating material provided by the present invention has good compatibility with the diaphragm and can be coated on the diaphragm to form a continuous and uniform coating, which can not only improve the compatibility between the diaphragm and the electrolyte, but also improve the mechanical strength, puncture strength and thermal stability of the diaphragm, and has the advantage of low cost, solving the problems of easy shedding of inorganic particle-coated diaphragms and high cost and poor compatibility of aramid material-coated diaphragms with diaphragms.
[0020] 2. The coating material provided by the present invention has strong adhesion, and the bonding strength between the coating formed after curing and the diaphragm is high, which is beneficial to improving the stability and safety of lithium batteries. Description of the drawings:
[0021] Figure 1These are optical photographs of the coatings formed after the coating materials prepared in Example 1 (A) and Comparative Example 2 (B) were coated on a base film and cured. Specific implementation method:
[0022] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] The present invention provides a method for preparing a coating material, the preparation method comprising:
[0025] A method for preparing a coating material, characterized in that the preparation method comprises:
[0026] In the presence of a protective gas, the functionalized inorganic particles, the first monomer and the second monomer are subjected to a first reaction in a solvent, and then a catalyst, a polymerization accelerator and a third monomer are added to conduct a second reaction to obtain the coating material;
[0027] The functionalized inorganic particles are inorganic particles with functional groups grafted onto their surfaces, and the functional groups are amino groups and / or carboxyl groups;
[0028] The first monomer is selected from at least one of diamine, triamine and tetraamine;
[0029] The second monomer is selected from at least one of dibasic acid chloride, tribasic acid chloride and tetrabasic acid chloride;
[0030] The structural formula of the third monomer is as follows:
[0031]
[0032] Among them, R 1 , R 2 and R 3 Each independently selected from at least one of a hydrocarbon group, an ether group and an aromatic group; R 4 is selected from an amino group or an acyl chloride group; m≤10, n≤10, p≤10, and m, n and p are not zero at the same time.
[0033] In the present invention, the first monomer is a polyamine, for example, it can be at least one of a diamine, a triamine and a tetraamine, preferably a diamine; further preferably, the diamine includes but is not limited to 2,2'-bis(trifluoromethyl)-(1,1'-diphenyl)-4,4'-diamine, 9,9-bis(3-fluoro-4-aminophenyl)fluorene, 9,9-bis(4-aminophenyl)fluorene, 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether, 1,6-hexanediamine, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 1 ,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diaminobiphenyl-2,2'-dicarboxylic acid, 4,4'-bis(4-aminophenoxy)biphenyl, 1,3-bis(3-aminophenoxy)benzene, 2-(4-aminophenyl)-5-aminobenzimidazole, 2,2-bis(4-hydroxy-3-aminophenyl)propane, 2-(4-aminophenyl)-5-aminobenzoxazole, 4,4'-bis(3-aminophenoxy)diphenyl sulfone, 3,4'-diaminodiphenyl ether, 9,9-dimethylfluorene-2,7-diamine, 4-aminobenzoic acid 4-aminophenyl ester, [4-(4-aminophenyl) 4-aminobenzoate, 1,2-phenylenediamine, 3,3'-dihydroxybenzidine, 3,3',5,5'-tetramethylbenzidine, N,N'-(2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diyl)bis(4-aminobenzamide), bis(4-aminophenyl) terephthalate, 4,4'-bis(3-aminophenoxy)biphenyl, 1,3-phenylenediamine, 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, N,N'-[[2,2,2-trifluoro-1-(trifluoromethyl)ethylidene]bis(6-hydroxy-3,1-phenylene)]bis[3-aminobenzamide], N,N'-[[2,2 At least one of 2,2-trifluoro-1-(trifluoromethyl)ethylidene]bis(6-hydroxy-3,1-phenylene)]bis[4-aminobenzamide], 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-diaminobenzanilide, 5(6)-1-(4-aminophenyl)-1,3,3-trimethylindane (indene diamine), 5(6)-amino-1-(4-aminophenyl)-1,3,3-trimethylindane (indene diamine), 3,5-diaminobenzoic acid, o-tolidine, 4,4'-diaminophenyl sulfone, 9,9-bis[4-(4-aminophenoxy)phenyl]fluorene, 1,4-phenylenediamine, 4,4'-diaminodiphenyl ether and 4,4'-diaminodiphenylmethane;Preferably, it is at least one of 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenyl ether, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, and 9,9-dimethylfluorene-2,7-diamine; In some preferred embodiments of the present invention, the first monomer is composed of at least two diamines. ;
[0034] Furthermore, in the present invention, the first monomer is composed of m-phenylenediamine (monomer A) and a diamine containing an ether unit (monomer B), and the molar amount of monomer A and monomer B should be controlled within a reasonable range. Under preferred conditions, based on the weight of the first monomer, the molar content of monomer A is 40-60 mol%, and the molar content of monomer B is 40-60 mol%.
[0035] The second monomer is selected from at least one of dibasic acid chlorides, tribasic acid chlorides and tetrabasic acid chlorides, preferably dibasic acid chlorides; further preferably, the dibasic acid chlorides include but are not limited to at least one of 1,4-benzenedicarboxylic acid dichloride, isophthaloyl chloride, 2,6-naphthalene dicarboxylic acid chloride, 4,4-biphenylacetyl chloride, adipoyl chloride, 1,4-cyclohexanediyl chloride, succinoyl chloride, 1,8-dioctanoyl chloride, 1,7-heptanedioyl chloride, dimethylmalonyl chloride and 2,5-furandicarboxylic acid chloride.
[0036] In the present invention, the addition of the third monomer can significantly increase the compatibility between the coating material and the polyolefin base film, reduce the construction difficulty, improve the yield rate, and improve the peel strength; the structural formula of the third monomer is as follows:
[0037]
[0038] Among them, R 1 , R 2 and R 3 Each independently selected from at least one of a hydrocarbon group, an ether group and an aromatic group; R 4 is selected from amino or acyl chloride, preferably acyl chloride; m, n and p are natural numbers, m≤10, n≤10, p≤10, and m, n and p are not zero at the same time.
[0039] Preferably, the R 1 , R 2 and R 3 At least one of them is a hydrocarbon group, and R 1 and R 3 Neither 2 same.
[0040] In the present invention, the hydrocarbon group may be an alkyl group or an alkenyl group, the alkyl group may be a straight-chain alkyl group or a branched-chain alkyl group, including but not limited to methylene and isopropyl; the alkenyl group may be a straight-chain alkenyl group or a branched-chain alkenyl group, including but not limited to vinyl and isobutylenyl.
[0041] The aromatic group includes, but is not limited to, phenyl, alkylphenyl, biphenyl, and naphthyl.
[0042] In some preferred embodiments of the present invention, the third monomer includes but is not limited to octadecanoyl chloride, 1-phenylcyclopentanecarbonyl chloride, hexanoyl chloride, decanoyl chloride, cyclohexylcarbonyl chloride, cyclohexylcarbonyl chloride, 2-oxocyclopentanecarbonyl chloride, 2-(1-adamantyl)acetyl chloride, lauroyl chloride, lauroyl chloride, 2-ethylhexanoyl chloride, tetradecanoyl chloride, acetyltropine chloride, 4-methoxyphenylacetyl chloride, phenylacetyl chloride, 3-methoxyphenylacetyl chloride, 1-phenylcyclobutanecarbonyl chloride, 1-phenylcyclopentanecarbonyl chloride, diphenylacetyl chloride, 1,3-benzodioxazol-5-yl acetyl chloride, naphth-1-yl acetyl chloride, isopropyl p-phenylacetyl chloride, 9-xanthene-9-yl chloride, 2-phenylbutyryl chloride, o-methoxyphenylacetyl chloride, 2-(3,4-dimethoxyphenyl)acetyl chloride, 4-butylbenzyl chloride, 4-pentyl At least one of benzoyl chloride, 4-hexylbenzoyl chloride, p-octylbenzoyl chloride, 4-n-decylbenzoyl chloride, 4-nonylbenzoyl chloride, 5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-2-naphthalenecarbonyl chloride, 4-n-heptylbenzoyl chloride, 2-ethoxyethyl 2-chloro-2-oxyylidene acetate, oxalyl chloride monomethyl ester, methoxyacetyl chloride, 2-(2-methoxyethoxy)acetyl chloride, 4-aminomethylphenylpropionic acid methyl ester, 4-tert-butylaniline, 4-n-pentylaniline, 4-n-butylaniline, 4-aminophenylethyl acetate, p-aminophenylacetic acid, 4-aminoacetophenone, 4-octylaniline, 4-hexylaniline, 7-amino-4-methylcoumarin, 4-heptylaniline, 4-aminoacetophenone, laurylamine, tetradecylamine, 1-adamantanylamine, hexadecylamine, aminoundecanoic acid, and octadeceneamine.
[0043] In the present invention, the polymerization accelerator can increase the reaction activity between the functional groups on the surface of the inorganic particles and the reactants in the solution, so that the properties of the obtained composite material are more uniform, which is beneficial to improving the flexibility, thermal stability, mechanical strength, coating uniformity and electrolyte wettability of the material-coated diaphragm; the polymerization accelerator is selected from at least one of polyether, cyclic crown ether and quaternary ammonium salt; preferably, the polymerization accelerator is selected from at least one of polyethylene glycol, polyethylene glycol alkyl ether, cyclodextrin, benzyltriethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride and tetradecyltrimethylammonium chloride.
[0044] In the present invention, the catalyst is selected from at least one of sodium hydroxide, calcium hydroxide, magnesium hydroxide, ammonia water, pyridine and 2-methylpyridine.
[0045] In the present invention, the solvent is selected from at least one of m-cresol, N-methylpyrrolidone, dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, water, methanol, ethanol, n-propanol, isopropanol, n-butanol, ethyl acetate, tetrahydrofuran, acetone, ether, butanone, cyclopentanone, dichloromethane, chloroform, petroleum ether, n-hexane, hexamethyldisiloxane, toluene and xylene.
[0046] In the present invention, the reaction temperature of the first reaction is -20 to 60°C, and the reaction time is 0.5 to 48 hours.
[0047] In the present invention, the reaction temperature of the second reaction is 0 to 100° C., and the reaction time is 6 to 48 hours.
[0048] In the present invention, the method for preparing the functionalized inorganic particles comprises: in the presence of a solvent, the inorganic particles are mixed evenly with a modifier and then subjected to a modification treatment.
[0049] Preferably, the modifier is selected from at least one of an aminosilane coupling agent, a carboxylsilane coupling agent, an aminosilane titanate coupling agent, a carboxylaminosilane titanate coupling agent and dopamine.
[0050] Preferably, the inorganic particles include but are not limited to at least one of aluminum oxide, iron oxide, titanium dioxide, aluminum hydroxide, boehmite and magnesium hydroxide; aluminum oxide and / or boehmite are further preferred; in order to avoid the defect of high hardness of inorganic particles, which may lead to battery short circuit and fire, the inorganic particles are preferably boehmite. In order to further avoid the introduction of magnetic foreign matter during operation, the boehmite is preferably boehmite provided by Anhui Yishitong Materials Technology Co., Ltd.
[0051] Preferably, the particle size of the inorganic particles is 5 nm-20 μm, more preferably 30 nm-5 μm.
[0052] Preferably, the weight ratio of the inorganic particles to the modifier is 20-200:1, for example, it can be 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, 110:1, 120:1, 130:1, 140:1, 150:1, 160:1, 170:1, 180:1, 190:1, 200:1 or any value in the range formed by any two of the above ratios.
[0053] Preferably, the treatment temperature of the modification treatment is 20-120° C., and the treatment time is 1-24 h.
[0054] The present invention provides a coating material obtained by the above-mentioned preparation method. The coating material comprises polyamide and inorganic particles filled in the polyamide. The weight ratio of the polyamide to the inorganic particles is 20:1 to 1:10, for example, it can be 20:1, 18:1, 15:1, 12:1, 10:1, 8:1, 5:1, 3:1, 2.5:1, 2:1, 1:1, 1.5:1, 1:2, 1:3, 1:5, 1:8, 1:10 or any value in the range of any two of the above ratios, preferably 1-5:1.
[0055] The present invention also provides the use of the aforementioned coating material in the preparation of lithium battery separators and pole piece edge coatings.
[0056] The present invention also provides a lithium battery separator, comprising a base film and a coating covering one side or both sides of the base film, wherein the base film is a polyolefin separator, and the coating is prepared from the aforementioned coating material. The thermal shrinkage ratio of the lithium battery separator at 150°C for 1 hour is not greater than 5%, and the thermal shrinkage ratio at 200°C for 1 hour is not greater than 10%. The polyolefin separator includes but is not limited to a polypropylene separator, a polyethylene separator, and a polyethylene / polypropylene composite separator.
[0057] The present invention will be described in detail below through examples.
[0058] In the following examples, the test method is as follows:
[0059] 1) Thermal shrinkage test
[0060] First, the diaphragm is cut into discs with a diameter of 19 mm using a punching machine, and its initial area S is calculated. 0 Then, the oven temperature is raised to the test temperature, the diaphragm disc sample is placed in the oven for 1 hour and then taken out, the diameter of the diaphragm after heat treatment is measured, and the corresponding area S is calculated. 1 , use the following formula to calculate the thermal shrinkage:
[0061]
[0062] 2) Puncture strength test
[0063] The needle puncture tester TA-JYZC-001 produced by Guangzhou Taian Yiqiao Energy Equipment Co., Ltd. was used. A square diaphragm with a width of 50 mm was fixed on the fixture, and the steel needle pierced the diaphragm at a speed of 2 mm / min, and the puncture strength of the diaphragm was recorded.
[0064] 3) Tensile strength test
[0065] The CMT6104 universal tensile testing machine produced by Mester Industrial Systems China Ltd. was used to cut the diaphragm into samples of 100 mm × 15 mm (length × width), and its tensile strength was tested at a speed of 50 mm / min.
[0066] 4) Peel strength test
[0067] A Labthink BLD-200N electronic peeling tester was used to take a square diaphragm with a width of 30 mm, and the sample and the tape were stretched at a speed of 2 mm / min, and the peeling strength of the diaphragm was determined based on the peeling force.
[0068] Example 1
[0069] (1) Preparation of functionalized boehmite A1: 180 g of deionized water and 20 g of ethanol were added to a three-necked flask, the pH was adjusted to 10 with aqueous ammonia, 0.3 g of 3-aminopropyltriethoxysilane was added, and after stirring at 30° C. for 5 min, 20 g of boehmite with a median particle size of 300 nm was added, the temperature was raised to 60° C. and stirred for 8 h, filtered, washed, and dried to obtain amino boehmite A1;
[0070] (2) Preparation of composite material B1: Argon was introduced into a four-necked flask, and 100 mL of dimethylacetamide was added, followed by the addition of 7.03 g (0.065 mol) of m-phenylenediamine, 13.02 g (0.065 mol) of 4,4'-diaminodiphenyl ether, 20 g of amide boehmite A1, and 0.14 g of tetrabutylammonium bromide. After cooling to -10°C, 26.65 g of isophthaloyl chloride was added, and 0.35 g of n-hexanoyl chloride was added after 20 min of reaction for 2 h. After the system returned to room temperature, calcium hydroxide powder was dispersed and mixed with 20 mL of dimethylacetamide, and the mixture was put into the flask and continued to react for 30 min. The mixture was washed with water, filtered, and dried to obtain composite material B1.
[0071] (3) Add N-methylpyrrolidone with a purity of 98% to the composite material B1 and mix well to obtain a coating material C1 with a solid content of 25%. Take a PE double-layer base film with a thickness of 12 μm (purchased from Shenzhen Xingyuan Material Technology Co., Ltd.) to prepare a composite film with a single-side coating thickness of 5 μm. Its performance parameters are shown in Table 1.
[0072] Examples 2-3 and Comparative Examples 1-2
[0073] The method of Example 1 is followed, except that the type and amount of the first monomer are as shown in Table 1, and the performance parameters thereof are as shown in Table 1.
[0074] Table 1
[0075]
[0076] From Table 1 we can see that:
[0077] The ratio of m-phenylenediamine to 4,4'-diaminodiphenyl ether should be strictly controlled within a specific range. When the amount of 4,4'-diaminodiphenyl ether exceeds half of the total amount of diamine monomers (molar value), it is beneficial to improve the peel strength, but it will lead to a decrease in the tensile strength, puncture strength and shrinkage rate of the composite film at 200°C. The reason is that the ether bond in 4,4'-diaminodiphenyl ether is conducive to breaking the regular arrangement of the polymer chain and playing a role in improving the adhesion.
[0078] When the amount of m-phenylenediamine exceeds half of the total amount (molar value) of diamine monomers, the peel strength decreases due to the reduction of ether bonds on the polymer chain.
[0079] When only 4,4'-diaminodiphenyl ether is used as the first monomer, a large number of ether-containing units will significantly reduce the puncture strength of the composite film and significantly increase the thermal shrinkage rate; when only m-phenylenediamine is used as the first monomer, the lack of ether-containing units makes the bonding force between the coating material and the base film very weak, resulting in the inability to prepare a composite film.
[0080] Figure 1 The optical photographs of the coating materials in Example 1 and Comparative Example 2 after coating. Figure 1 It can be seen that compared with Comparative Example 2 in which no 4,4' diaminodiphenyl ether is added, the coating uniformity of the coating material obtained in Example 1 is better.
[0081] Examples 4-5 and Comparative Examples 3-4
[0082] The method of Example 1 is followed, except that the amount of the third monomer n-hexanoyl chloride used is as shown in Table 2, and its performance parameters are as shown in Table 2.
[0083] Table 2
[0084]
[0085]
[0086] It can be seen from Table 2 that when the third monomer is reduced, the mechanical properties of the composite film deteriorate, and the peel strength decreases significantly, indicating that the addition of the third monomer is beneficial to improving the bonding force between the coating and the base film; however, the third monomer should not be added too much, because the addition of too much third monomer not only fails to improve the mechanical strength and adhesion of the composite film, but reduces the mechanical properties and peel strength of the composite film; in addition, not adding the third monomer will affect the bonding force between the coating and the base film, resulting in a significant decrease in the peel strength and worsening the thermal stability of the composite film.
[0087] Embodiment 6-8
[0088] The method of Example 1 is followed, except that the type of the third monomer is different, as shown in Table 3.
[0089] Table 3
[0090]
[0091] It can be seen from Table 3 that the use of a third monomer containing an alkyl chain, a benzene ring or an ether bond can improve the mechanical properties and peel strength of the composite film.
[0092] Examples 9-10 and Comparative Example 5
[0093] The method of Example 1 is followed, except that the amount of the modifier 3-aminopropyltriethoxysilane used is as shown in Table 4.
[0094] Table 4
[0095]
[0096] It can be seen from Table 4 that: when the amount of modifier is too small, boehmite cannot effectively form a covalent bond with the polymer, resulting in a decrease in the mechanical properties of the composite membrane; when the amount of modifier is further increased, the amount of active amino groups in the reaction system is increased, resulting in a decrease in the molecular weight of the polymer, thereby affecting the mechanical properties of the composite membrane, and the effect is greater than that of reducing the amount of modifier; and when no modifier is used, the performance indicators of the composite membrane are significantly reduced.
[0097] Examples 11-12 and Comparative Example 6
[0098] The method of Example 1 is followed, except that the amount of functionalized boehmite A1 added is as shown in Table 5.
[0099] Table 5
[0100]
[0101] It can be seen from Table 5 that the amount of functionalized boehmite has a significant effect on the puncture strength of the composite membrane. When no functionalized boehmite is added or the amount of functionalized boehmite is too small, the puncture strength of the composite membrane is significantly reduced; when the amount of functionalized boehmite is too large, the puncture strength does not change significantly, and the increase in inorganic particles will lead to a weakening of the bonding force between the coating and the base membrane, but the addition of inorganic particles can enhance the thermal stability of the composite membrane.
[0102] Embodiment 13
[0103] The method of Example 1 was followed, except that alumina was used instead of boehmite. The performance parameters of the composite membrane are shown in Table 6.
[0104] Table 6
[0105]
[0106] It can be seen from Table 6 that no matter whether the inorganic particles are boehmite or alumina, the mechanical properties and thermal stability of the composite membrane can be significantly improved after functional modification, but compared with alumina, boehmite can further improve the mechanical properties and thermal stability of the composite membrane.
[0107] Comparative Example 7
[0108] (1) The preparation of functionalized boehmite A1 is the same as in Example 1;
[0109] (2) Preparation of polyamide B2: Argon was introduced into a four-necked flask, and 100 mL of dimethylacetamide was added, followed by the addition of 7.03 g of m-phenylenediamine and 13.02 g of 4,4'-diaminodiphenyl ether. After cooling to -10°C, 26.65 g of isophthaloyl chloride was added, and after 20 minutes, 0.35 g of n-hexanoyl chloride was added to react for 2 hours. After the system returned to room temperature, calcium hydroxide powder was dispersed and mixed with 20 mL of dimethylacetamide, and the mixture was put into the flask and continued to react for 30 minutes. The mixture was washed with water, filtered, and dried to obtain polyamide B2.
[0110] (3) 20 g of functionalized boehmite A1 and polyamide B2 were added to N-methylpyrrolidone with a purity of 98%, and mixed evenly to obtain a coating material C2 with a solid content of 25%. A base film with a thickness of 12 μm was taken to prepare a composite film with a single-side coating thickness of 5 μm. Its performance parameters are shown in Table 7.
[0111] Table 7
[0112]
[0113] It can be seen from Table 7 that the coating material obtained by physical mixing of functionalized boehmite and polyamide has poor adhesion to the base film due to the poor compatibility of functionalized boehmite and polyamide, resulting in a decrease in the peel strength between the coating and the base film, and also causing a significant decrease in the puncture strength and thermal stability of the composite film.
[0114] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a coating material, characterized in that: The preparation method comprises: In the presence of a protective gas, the functionalized inorganic particles, the first monomer and the second monomer are subjected to a first reaction in a solvent, and then a catalyst, a polymerization accelerator and a third monomer are added to conduct a second reaction to obtain the coating material; The functionalized inorganic particles are inorganic particles with functional groups grafted onto their surfaces, and the functional groups are amino groups and / or carboxyl groups; The first monomer is composed of monomer A metaphenylenediamine and monomer B diamine containing an ether unit, and based on the weight of the first monomer, the molar content of the monomer A is 40-60 mol%, and the molar content of the monomer B is 40-60 mol%; The second monomer is selected from at least one of dibasic acid chloride, tribasic acid chloride and tetrabasic acid chloride; The structural formula of the third monomer is as follows: Wherein, R1, R2 and R3 are each independently selected from at least one of a hydrocarbon group, an ether group and an aromatic group; R4 is selected from an amino group or an acyl chloride group; m≤10, n≤10, p≤10, and m, n and p are not zero at the same time; The polymerization accelerator is selected from at least one of polyethylene glycol, polyethylene glycol alkyl ether, cyclodextrin, benzyltriethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride, and tetradecyltrimethylammonium chloride; The catalyst is selected from at least one of sodium hydroxide, calcium hydroxide, magnesium hydroxide, ammonia water, pyridine and 2-methylpyridine.
2. The preparation method according to claim 1, characterized in that: The dibasic acid chloride is selected from at least one of 1,4-benzenedicarboxylic acid dichloride, isophthaloyl chloride, 2,6-naphthalene dicarboxylic acid chloride, 4,4-biphenylacetyl chloride, adipoyl chloride, 1,4-cyclohexanediyl chloride, succinoyl chloride, 1,8-dioctanoyl chloride, 1,7-heptanedioyl chloride, dimethylmalonyl chloride, and 2,5-furandicarboxylic acid chloride.
3. The preparation method according to claim 1, characterized in that: At least one of R1, R2 and R3 is a hydrocarbon group, and R1 and R3 are not the same as R2.
4. The preparation method according to claim 1, characterized in that: The solvent is selected from at least one of m-cresol, N-methylpyrrolidone, dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, water, methanol, ethanol, n-propanol, isopropanol, n-butanol, ethyl acetate, tetrahydrofuran, acetone, ether, butanone, cyclopentanone, dichloromethane, chloroform, petroleum ether, n-hexane, hexamethyldisiloxane, toluene and xylene.
5. The preparation method according to claim 1, characterized in that: The reaction temperature of the first reaction is -20 to 60°C, and the reaction time is 0.5 to 48 hours.
6. The preparation method according to claim 1, characterized in that: The reaction temperature of the second reaction is 0-100° C., and the reaction time is 6-48 hours.
7. The preparation method according to claim 1, characterized in that: The method for preparing the functionalized inorganic particles comprises: in the presence of a solvent, the inorganic particles are mixed evenly with a modifier and then subjected to a modification treatment.
8. The preparation method according to claim 7, characterized in that: The modifier is selected from at least one of an aminosilane coupling agent, a carboxylsilane coupling agent, an aminosilane titanate coupling agent, a carboxylaminosilane titanate coupling agent and dopamine.
9. The preparation method according to claim 7, characterized in that: The inorganic particles are selected from at least one of aluminum oxide, iron oxide, titanium dioxide, aluminum hydroxide, boehmite and magnesium hydroxide.
10. The preparation method according to claim 9, characterized in that: The inorganic particles are alumina and / or boehmite.
11. The preparation method according to claim 7, characterized in that: The particle size of the inorganic particles is 5 nm-20 μm.
12. The preparation method according to claim 11, characterized in that: The particle size of the inorganic particles is 30 nm-5 μm.
13. The preparation method according to claim 7, characterized in that: The weight ratio of the inorganic particles to the modifier is 20-200:
1.
14. The preparation method according to claim 7, characterized in that: The treatment temperature of the modification treatment is 20-120° C., and the treatment time is 1-24 hours.
15. A coating material obtained by the preparation method according to any one of claims 1 to 14.
16. The coating material according to claim 15, characterized in that: The coating material includes polyamide and inorganic particles filled in the polyamide.
17. The coating material according to claim 16, characterized in that: The weight ratio of the polyamide to the inorganic particles is 20:1 to 1:
10.
18. The coating material according to claim 17, characterized in that: The weight ratio of the polyamide to the inorganic particles is 1-5:
1.
19. Use of the coating material according to any one of claims 16 to 18 in the preparation of lithium battery separators and electrode edge coatings.
20. A lithium battery separator, comprising a base film and a coating covering one side or both sides of the base film, wherein the base film is a polyolefin separator, characterized in that: The coating is prepared from the coating material according to any one of claims 16 to 18.
21. The lithium battery separator according to claim 20, characterized in that: The thermal shrinkage ratio of the lithium battery separator when kept at 150° C. for 1 hour is not greater than 5%, and the thermal shrinkage ratio when kept at 200° C. for 1 hour is not greater than 10%.
Citation Information
Patent Citations
Lithium ion battery diaphragm with high-temperature-resistant coating, and preparation method of lithium ion battery diaphragm
CN111509168A
Modified para-aramid polymer solution, coating slurry, lithium battery diaphragm and preparation method of lithium battery diaphragm
CN112694610A